First report of caper (Capparis spinosa) serious infestation by Eurydema eckerleini in Cyclades Islands, Greece (Hemiptera: Heteroptera, Pentatomidae) - Simoglou, Konstantinos B.; Dioli, Paride (Fragmenta entomologica, 2017)
The islands of Tinos and Syros in the Cyclades Archipelago, Greece, have a hilly terrain, a mild Mediterranean climate and vegetation adapted to drought conditions. Caper (Capparis spinosa L.) is highly adapted to arid environments and grows successfully during the Mediterranean summer. In August 2015, we detected serious infestations on wild caper by Eurydema eckerleini (Pentatomidae), which was formerly considered a species endemic to Crete and the Peloponnese, with an isolated report in Turkey. This is the first record of the presence of E. eckerleini in the Cyclades.